Interactions among chronic and acute impacts on coral recruits: the importance of size-escape thresholds - Christopher Doropoulos; Selina Ward; Alyssa Marshell; Guillermo Diaz-Pulido; Peter John Mumby (PANGAEA, 2012)
Newly settled recruits typically suffer high mortality from disturbances, but rapid growth reduces their mortality once size-escape thresholds are attained. Ocean acidification (OA) reduces the growth of recruiting benthic invertebrates, yet no direct effects on survivorship have been demonstrated. We tested whether the reduced growth of coral recruits caused by OA would increase their mortality by prolonging their vulnerability to an acute disturbance: fish herbivory on surrounding algal turf. After two months extquotesingle growth in ambient or elevated CO2 levels, the linear extension and calcification of coral (Acropora millepora) recruits decreased as CO2 partial pressure (pCO2) increased. When recruits were subjected to incidental fish grazing, their mortality was inversely size dependent. However, we also found an additive effect of pCO2 such that recruit mortality was higher under elevated pCO2 irrespective of size. Compared to ambient conditions, coral recruits needed to double their size at the highest pCO2 to escape incidental grazing mortality. This general trend was observed with three groups of predators (blenny, surgeonfish, and parrotfish), although the magnitude of the fish treatment varied among species. Our study demonstrates the importance of size-escape thresholds in early recruit survival and how OA can shift these thresholds, potentially intensifying population bottlenecks in benthic invertebrate recruitment.
Supplement to: Doropoulos, C et al. (2012): Interactions among chronic and acute impacts on coral recruits: the importance of size-escape thresholds. Ecology, 93(10), 2131-2138, https://doi.org/10.1890/12-0495.1